EFEKTIVITAS PENGGUNAAN FITUR QR CODE DALAM MENGHIMPUN DANA ZIS DI LAZISNU KUDUS - Fatmawati, Putri Oktaviani; Qomar, Mohammad Nurul (Universitas Islam Raden Rahmat, 2024)
Technological development has brought changes to payment systems that used to use cash to become non-cash systems. This has had an impact on zakat institutions, especially LAZISNU, which has kept up with the distribution media. However, in using the QR Code there are problems that arise, due to the limited knowledge of the community about technology is still minimal, where the still do not know how to use the QR Code and how to measure its effectiveness. The purpose of this study is to determine the effectiveness of using the QR Code feature at LAZISNU in collecting zakat, infaq and alms funds. The research method used is descriptive qualitative with a case study approach. The results of this study indicate that the use of the QR Code at LAZISNU can be said to be effective. However, the lack of knowledge and uneven distribution means that the QR Code is still not widely known by the public. So that the use of INUK cans is still a priority for the community.